The formation and coalescence sites of the first gravitational wave events. (26th July 2017) - Schneider, Raffaella; Graziani, Luca; Marassi, Stefania; Spera, Mario; Mapelli, Michela; Alparone, Matteo; Bennassuti, Matteo de
Abstract: We present a novel theoretical model to characterize the formation and coalescence sites of compact binaries in a cosmological context. This is based on the coupling between the binary population synthesis code SeBa with a simulation following the formation of a Milky Way-like halo in a well-resolved cosmic volume of 4 cMpc, performed with the GAMESH pipeline. We have applied this technique to investigate when and where systems with properties similar to the recently observed LIGO/VIRGO events are more likely to form and where they are more likely to reside when they coalesce. We find that more than 70 per cent of GW151226 and LVT151012-like systems form in galaxies with stellar mass M *  > 10 8  M⊙ in the redshift range [0.06–3] and [0.14–11.3], respectively. All GW150914-like systems form in low-metallicity dwarfs with M *  < 5 × 10 6  M⊙ at 2.4 ≤ z ≤ 4.2. Despite these initial differences, by the time they reach coalescence the observed events are most likely hosted by star-forming galaxies with M *  > 10 10  M⊙ . Due to tidal stripping and radiative feedback, a non-negligible fraction of GW150914-like candidates end-up in galaxies with properties similar to dwarf spheroidals and ultrafaint satellites.